MEMAHAMI PERAN KUALITAS VISUAL DALAM MENINGKATKAN PENGALAMAN PENGGUNA VR PADA PRESENTASI DESAIN INTERIOR - Pramalystianto, Andhika (Universitas Mercu Buana, 2024)
With the development of digital technology, Virtual Reality (VR) has become an innovative tool in interior design presentation and exploration. VR allows users to interact with the space immersively, providing a more realistic experience compared to two-dimensional representations. One of the main factors that affects the quality of the user experience in VR is visual resolution. Higher resolution can increase the level of realism, clarifying material details, lighting, and textures, and reducing distracting visual effects, such as pixelation or blur. In the context of interior design, an optimal visual experience is essential to help designers and clients understand the scale, composition, and atmosphere of a space before the realization stage. Therefore, this study aims to explore the extent to which visual resolution in VR can affect user perception and interaction, and how optimizing display quality can improve the effectiveness of VR as an interior design presentation tool. The research method includes data collection through questionnaires, observations, and experiments on interior design users. The results of the study show that the use of high resolution directly increases respondents' interest and the effectiveness of using VR as a visualization tool in interior design. This shows the great potential of VR technology in enhancing the virtual interaction experience, as well as providing important directions in the selection of visualization media in the future. With high resolution, VR is able to provide a more realistic and immersive visual experience for users, which in turn can improve the understanding and appreciation of interior design. These findings provide a foundation for further development in the application of VR technology in the design industry, as well as emphasizing the importance of considering the visual resolution factor in its use. Thus, this study not only provides new insights, but also offers practical contributions to the development of VR in the context of interior design.